How policies influence smallholder farmers’ access to and use of genetic resources in three East African countries - Otieno, Gloria; Sikinyi, Evans; Vernooy, Ronnie; Fadda, Carlo; Halewood, Michael (2023)
This report addresses key policy issues around the access and use of genetic resources and their up-scaling for direct use and commercialization. It analyzes the current policy environment in Kenya, Uganda and Tanzania and identifies key policy-related gaps and challenges related to the utilization of genetic resources, and further proposes a strategy/roadmap for policy and institutional reforms to address these gaps and challenges.